Fiscal Federalism in Belgium Main Challenges and Considerations for Reform - Leibfritz, Willi (OECD Publishing, 2009)
The paper discusses the current state of fiscal relations across levels of government in Belgium and how it has developed over time. As the current system of fiscal federalism is creating imbalances between the federal and the sub-federal governments (vertical imbalance), and between sub-federal governments (horizontal imbalance) the paper also suggests directions for improvements. Without reform, the vertical imbalance will widen as the fiscal burden from the ageing of the population falls mainly on the federal level. Reform should therefore strengthen the fiscal capacity of the federal government by improving its revenue sources and by shifting some spending obligations to sub-federal governments. The imbalance between regions arises because of the lack of coherence between taxation and spending. Shared revenues from the personal income tax are allocated to the region of residence, while the region of the workplace does not benefit, which particularly affects Brussels' revenue level. This imbalance could be eliminated by allocating more of the shared personal income tax to the region of the workplace. Furthermore, the system of equalisation grants should be re-designed to provide incentives to the recipient regions to develop their own revenue base. The performance of the fiscal system could further be improved by raising the efficiency of spending in areas of national interest, which have been assigned to sub-federal governments or where there are overlapping responsibilities, such as in employment, R&D, training, education, energy and environmental policies
Keywords: Economics; Belgium